Experimental Validation of a Numerical Model to Predict the Performance of Solar PV Cells - Asim, Muhammad; Usman, Muhammad; Hussain, Jafar; Farooq, Muhammad; Naseer, Muhammad Irfan; Fouad, Yasser; Mujtaba, M.A.; Almehmadi, Fahad Awjah (Frontiers in Energy Research, 2022)
The models designed to evaluate the performance of photovoltaic (PV) cells depend on classical thermal principles with the use of constant optical coefficients (reflectance, absorbance, and transmittance). However, these optical coefficients depend on incident angle actually and, hence, are a function of the inclination and orientation of the PV panel along with the geographical location and time of the day. In this study, varying coefficients (optical thermal model) and constant coefficient (classical thermal model) with incident angle in the energy balance equations followed by experimental validation were considered. First, the incident angle of direct radiation on the PV panel was determined with the help of astronomic simplified calculations, and second, the optical coefficients were evaluated by using principles of classical electromagnetic theory. Third, the energy balance equations were expressed in the form of differential equations and solved numerically by the Runge–Kutta method to obtain the electrical power as a function of time. Finally, electrical power produced by the optical–thermal model and classical thermal model was validated against experimental data for the solar PV system installed at the Central Station, Punjab Emergency Service. The results show that there is significant agreement between the classical thermal model and experimentally produced electricity throughout the year which validates the modeling.